A novel particle swarm optimization based robust H‐infinity control for rotorcrafts. Issue 4 (2014) - Jiyang Dai; Jin Ying; Chang Tan
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this paper is to present a novel optimization approach to design a robust H‐infinity controller. Design/methodology/approach – To use a modified particle swarm optimization (PSO) algorithm and to search for the optimal parameters of the weighting functions under the circumstance of the given structures of three weighting matrices in the H‐infinity mixed sensitivity design. Findings – This constrained multi‐objective optimization is a non‐convex, non‐smooth problem which is solved by a modified PSO algorithm. An adaptive mutation‐based PSO (AMBPSO) algorithm is proposed to improve the search accuracy and convergence of the standard PSO algorithm. In the AMBPSO algorithm, the inertia weights are modified as a function with the gradient descent and the velocities and positions of the particles. Originality/value – The AMBPSO algorithm can efficiently solve such an optimization problem that a satisfactory robust H‐infinity control performance can be obtained. <ack> <x xml:space="preserve"> Acknowledgements </x> This work was supported by the National Natural Science Foundation of China (61164015) and the Aeronautical Science Foundation of China (2011ZA56021). </ack>